Some issues of improving the criminal law standards regulated by Article 320 of the Penal Code of the Republic of Kazakhstan «Failure to assist sick person» - Yespergenova, Е.V. (Bulletin of the Karaganda University “Law Series”, 2018)
The purpose of this work is to develop scientific-based proposals to improve criminal legislation and practice of its application. Based on the results of the research the author offers recommendations for improving the current criminal legislation and legal precedents in issues of crossing for failure to assist sick person, in particular, the author's position on the concept, type and amount of the assistance provided is proposed. In addition, considering the analysis of the existing points of view of academic lawyers, a number of conclusions were drawn related to the definition of the concepts «sick person» and «patient», on the basis of which the author proposed his own vision of this concept. The conclusions, results, provisions reflected in the work are based on the analysis of the legal literature, the materials of law enforcement practice and the survey of the relevant circle of respondents and can be used in further scientific research, when developing proposals for legislation, in the teaching process while teaching the criminal law course.